Cuando México se (re)apropia de Texas : ensayos - Boullosa, Carmen (Arte Público Press, 2015)
Residents on both sides of the Rio Grande, or the Rio Bravo as it's known in Mexico, have suffered horrific violence as numerous peoples have sought control of the land. In 1836, in what is now Texas, a young girl named Cynthia Ann Parker was kidnapped by Comanches who behaved "like vengeful drug dealers," spearing, scalping and castrating their victims. Spared death, she was adopted by the tribe, only to be "saved" twenty years later by the Texas Rangers. Today, kidnappings continue in Mexico. In this wide-ranging collection of 29 essays, internationally renowned Mexican novelist and essayist Carmen Boullosa explores issues that unite and separate Americans and Mexicans, from the nineteenth century to the present. Themes of greed and barbarism abound. There's Dimaso Salazar, a Mexican captain who in 1841 strung the ears of fallen Texans on a necklace; Susana Chavez, a poet and activist brutally murdered after protesting the killings of women in Ciudad Juarez; and Edelmiro Cavazos, the mayor of the city of Santiago, who was executed during Mexico's ruthless drug wars. Violence is still common on both sides of the border. These thought-provoking essays delve into a variety of subjects, including Occupy Wall Street and Arizona's political offensive against immigrants. Long a feminist, Boullosa also shares her perspective on women's rights, musing on the repression of women artists and the lack of recognition for their work. Similarly, women who participated in wars and rebellions have been forgotten, and the author asserts that erasing them from our memory hurts us all. Containing the author's original Spanish and Nicolas Kanellos' English translation, these are absorbing reflections on Texas-Mexico border history, women's issues, art and literature.